Biocompatibility Evaluation of 3 Facial Silicone Elastomers - Campos Franca, Diurianne Caroline [UNESP]; Castro, Alvimar Lima de [UNESP]; Soubhia, Ana Maria Pires [UNESP]; Tucci, Renata [UNESP]; Coelho Avila de Aguiar, Sandra Maria Herondina [UNESP]; Goiato, Marcelo Coelho [UNESP] (Lippincott Williams & Wilkins, 2011)
The failure of facial prostheses is caused by limitations in the properties of existing materials, especially the biocompatibility. This study aimed to evaluate the biocompatibility of maxillofacial silicones in subcutaneous tissue of rats. Thirty Wistar rats received subcutaneous implants of 3 maxillofacial silicone elastomers (LIM 6050, MDX 4-4210, and industrial Silastic 732 RTV). A histomorphometric evaluation was conducted to analyze the biocompatibility of the implants. Eight areas of 60.11 mm(2) from the surgical pieces were analyzed. Mesenchymal cells, eosinophils, and foreign-body giant cells were counted. Data were submitted to analysis of variance and Tukey test. Initially, all implanted materials exhibited an acceptable tissue inflammatory response, with tissue reactions varying from light to moderate. Afterward, a fibrous capsule around the silicone was observed. The silicones used in the current study presented biocompatibility and can be used for implantation in both medical and dental areas. Their prosthetic indication is conditioned to their physical properties. Solid silicone is easier to adapt and does not suffer apparent modifications inside the tissues.
Keywords: Facial silicone; connective tissue; biocompatibility; inflammation